Personalities of the woods : a collection of Bethlehem Pacific wire rope advertisements that contain personality sketches - Holbrook, Stewart H., 1893-1964 (Booklet, 1950)
"In each of these ads a prominent timberman with a colorful background has been interestingly spotlighted by Stewart Holbrook, internationally-known author and journalist"--P. [1].